2011
DOI: 10.1093/infdis/jir240
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of BCG Vaccination at Birth to Low-Birth-Weight Children: Beneficial Nonspecific Effects in the Neonatal Period?

Abstract: Though early BCG did not reduce infant mortality significantly, it may have a beneficial effect in the neonatal period. This could be important for public health because BCG is often delayed in low-income countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
470
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 521 publications
(505 citation statements)
references
References 34 publications
18
470
1
4
Order By: Relevance
“…78 Whereas in low birth weight neonates it reduced the mortality by almost 50% as demonstrated by fewer cases of sepsis and respiratory infections. 79,80 This is similar to results in adult mouse models of heterologous immunity where it was demonstrated that BCG-immune mice were more resistant to vaccinia virus infection and that this resistance was mediated by IFNg-producing CD4 T cells. 81 Interestingly, Steenhuis and others showed that in children, by 18 months of age, immunization with BCG resulted in lowered numbers of children with eczema, a Th2-immune mediated disease.…”
Section: Measles Vaccinesupporting
confidence: 82%
See 1 more Smart Citation
“…78 Whereas in low birth weight neonates it reduced the mortality by almost 50% as demonstrated by fewer cases of sepsis and respiratory infections. 79,80 This is similar to results in adult mouse models of heterologous immunity where it was demonstrated that BCG-immune mice were more resistant to vaccinia virus infection and that this resistance was mediated by IFNg-producing CD4 T cells. 81 Interestingly, Steenhuis and others showed that in children, by 18 months of age, immunization with BCG resulted in lowered numbers of children with eczema, a Th2-immune mediated disease.…”
Section: Measles Vaccinesupporting
confidence: 82%
“…However, the observational studies in rural Guinea-Bissau indicated that the presence of vaccinia scars were associated with increased survival rates among adults. 79,83 It was also shown that it may decrease the risk of asthma and malignant melanoma. 84 In Danish studies, smallpox immunizations lowered the number of infectious disease hospitalizations.…”
Section: Vaccinia Vaccinationsmentioning
confidence: 99%
“…Previous studies have shown that BCG has beneficial non-specific or heterologous effects, providing protection also against many non-tuberculosis causes of death: in randomized trials of early BCG to low-birth-weight children, BCG at birth versus delayed BCG, as is normal practice, decreased neonatal mortality by 38% (17–54%) [3739]. With most infant deaths occurring during the neonatal period [40] and with less than half of children vaccinated during the first two weeks of life, most children do not benefit from BCG when they are most at risk.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the information supporting these ideas has come from observational studies because of the difficulty in conducting placebo controlled trials with established vaccines, but a recent randomized trial of BCG given to low birth weight babies showed a significant reduction in neonatal but not in infant mortality [18]. Acceptance of the results of these studies has, until recently, been met with some scepticism because of the lack of an apparent mechanism through which these effects could be achieved.…”
Section: (C) the Expanded Programme On Immunizationmentioning
confidence: 99%